2013
DOI: 10.1016/j.ajog.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a multivariate index assay on referral patterns for surgical management of an adnexal mass

Abstract: OBJECTIVE:To determine the impact on referral patterns of using a Multivariate Index Assay, CA125, modified-American College of Obstetricians and Gynecologists referral guidelines, and clinical assessment among patients undergoing surgery for an adnexal mass after initial evaluation by nongynecologic oncologists.STUDY DESIGN: Overall, 770 patients were enrolled by nongynecologic oncologists from 2 related, multiinstitutional, prospective trials and analyzed retrospectively. All patients had preoperative imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
(24 reference statements)
3
11
0
1
Order By: Relevance
“…As compared with findings from Bristow et al 11 and Im et al, 9 the ACOG/SGO guidelines yielded a higher PPV among the present study population, which would be expected given the higher prevalence of malignancy at JHS Hospital. These findings highlight the challenge of developing a standardized algorithm that is fully generalizable and applicable to all patient populations given the inherently different a priori risks of malignancy in various hospital settings.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As compared with findings from Bristow et al 11 and Im et al, 9 the ACOG/SGO guidelines yielded a higher PPV among the present study population, which would be expected given the higher prevalence of malignancy at JHS Hospital. These findings highlight the challenge of developing a standardized algorithm that is fully generalizable and applicable to all patient populations given the inherently different a priori risks of malignancy in various hospital settings.…”
Section: Discussionsupporting
confidence: 73%
“…As compared with findings from Bristow et al . and Im et al., the ACOG/SGO guidelines yielded a higher PPV among the present study population, which would be expected given the higher prevalence of malignancy at JHS Hospital.…”
Section: Discussionsupporting
confidence: 71%
“…In a trial of almost 500 patients set to undergo surgery for an adnexal mass, OVA1 demonstrated higher sensitivity and a negative predictive value for ovarian malignancy compared to clinical impression and other blood marker (CA-125) measurements in a population of nongynecologic oncology practices. 8 OVA1 generates a numeric result and categorizes patient risk of malignancy (high vs. low) stratified by menopausal status (pre vs. post). OVA1 has been approved for use in clinical practice since 2009 and has been validated for use by nongynecologic oncologists in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…OVA1 has been approved for use in clinical practice since 2009 and has been validated for use by nongynecologic oncologists in several studies. 8 However, the extent to which it is used by physicians to evaluate whether a patient needs to be referred to a gynecologic oncologist before surgery has not been measured.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, 15.4% of the entire population is > 65 years old, and, as of 2017, life expectancy for women at birth is 81.8 years [ 1 ]. The demand for care of pelvic floor disorders has been projected to increase by 35% between 2010 and 2030 [ 2 ]. There are many surgical options for POP treatment–both native tissue and synthetic mesh operations.…”
Section: Introductionmentioning
confidence: 99%